Konsep Jiwa dan Etika Islam dalam Pembentukan Kepribadian menurut Imam al-Ghazali - Shidiq, Muh.; Syafii, Much.; Sudiarto, Sudiarto; Mujiburrohman, Mujiburrohman (TSAQOFAH, 2026)
The concept of the soul and Islamic ethics according to Imam Al-Ghazali is highly relevant to the formation of human personality, particularly in the context of character education in the modern era. This study aims to provide an in-depth analysis of Al-Ghazali’s structure of the soul, which encompasses the faculties of reason, anger, and desire, and to explain how these three are refined and balanced through Islamic ethics to produce a mature and moral personality, while also elucidating Al-Ghazali’s contribution to the development of akhlak and contemporary character education. This research employs a qualitative method with a library research approach, drawing primarily on Al-Ghazali’s major works such as Ihya’ Ulumuddin, Mizan al-‘Amal, and Kimya’ al-Sa‘adah, which are further enriched by secondary literature in the form of journals, books, and previous studies on Islamic ethics and psychology. The analysis shows that, in Al-Ghazali’s view, the human soul contains both good and bad potentials that must be directed through the purification of the heart (tazkiyah al-nafs) and the control of base desires, with Islamic ethics functioning as a practical guide for shaping behavior through moral training, habituation to virtuous deeds, and the purification of intention. Personality formation is understood as a spiral process that requires continuous balance among spiritual, intellectual, and emotional potentials. These findings affirm that Al-Ghazali’s thought is highly relevant to contemporary character education because it emphasizes the integration of moral and spiritual dimensions as the foundation of personality, thereby offering an important contribution to efforts to cultivate individuals who are morally upright, wise, and emotionally stable.